Survival analysis in product life cycle investigations: An assessment of robustness for the German automobile industry - Jens Krüger (Technische Universität Darmstadt, Department of Law and Economics, 2015)
We apply various refinements of survival regression to assess the results of some basic specifications based on product life cycle theory for the case of a data set of the German automobile industry. The methods applied pay attention to biases in the coefficient estimates and the standard errors, the discrete nature of the duration data and the presence of unobserved heterogeneity. Robust estimation methods are also applied. We find that that the coefficient estimates and standard errors are not much affected by applying the renewed estimators. The substantial results of a previous study with the same data are unchanged.
urn:nbn:de:tuda-tuprints-47032
Keywords: C41; C25; C14; L10; L62; O33; 330; firm survival; Cox regression; robustness assessment